Polymer clay jewelry : the ultimate guide to making wearable art earrings - Skidmore, Rachael (Art makers., 2023)
Master the art of making earrings from polymer clay with Polymer Clay Jewelry, written and created by Rachael Skidmore of the popular online shop Made by Maeberry.